Different nuclease activities in competent and noncompetent Bacillus subtilis. - Joenje, H (1975)
Competent and noncompetent cells of Bacillus subtilis were separated on the basis of their different buoyant densities. The two types of cells were compared with respect to their interactions with exogenous deoxyribonucleic acid(DNA). After exposure of DNA to the cells, the unadsorbed fraction of DNA molecules was examined. Both types of cells decreased the biological activity of this DNA, the inactiviation exerted by noncompetent cells being more severe than that exerted by competent cells. Sedimentation analysis of the inactivated DNA revealed that fragments of DNA are produced, owing mainly to the introduction of double-strand scissions. In addition to this fragmentation, the competent bacteria extensively digested the DNA exonucleolytically. This type of breakdown was specifically related to the competent state rather than to the state of low density. The exonucleolytic activity is, in all probability, associated with the cell envelope, because most of the activity is released into the medium when the cells are converted to protoplasts. At 37 C the competence-specific exonucleolytic breakdown started 2 to 3 min after the binding of DNA to the cells. In unfractionated cultures, breakdown may proceed until 70% of the total amount of DNA added has been made acid soluble. Nontransforming Escherichia coli DNA was also subject to exonucleolytic degradation; it seems unlikely,therefore, that this type of breakdown occurs as a consequence of recombination. Since ethylenediaminetetraacetate blocked both transformation by native DNA and the exonucleolytic breakdown of bound DNA, we suggest that the breakdown of DNA by competent cells fulfills an essential function in genetic transformation of B. subtilis.